Die Eigenart Goas - Ribeiro, Orlando (ERDKUNDE, 1963)
During its good old days (XVII th. century) Goa was the most important Portuguese city. Today, however, from its splendour only its stateley and sumptuous churches remain in the middle of a desert grove of palm tres. Rather, confronting a hostile and impenetrable world the city, at the most central part of the ocean it once had longed to dominate, took advantage of its marginal situation. Through a weak half-breed opposed to by a system of castes but compensated for a religious assimilation together with its custom and ways of thinking, a Christian Society was brought forth into the city and its fertile plains, which form its rural surroundings, and where the Inquisition endeavoured to expurgate the tenacious traces of the atavic Hinduism. Thus, the Old Conquest, a center of proselytism and evangelistic ambition that History throug hout its course would take on to deny, have left an indel ible Christian mark in this corner of India. The churches and their parishes, often built on the site of the Hindu temples destroyed, and facing the gentiles' land, only separeted from it by the smooth waters of the estuaries, erect in a challeng, their stately and magnificient facades. However, a profusion of rustic chapels, some at the top of the hills, of large crosses set up in roads, of niches in the bridges and dams which protect the plains, express everywhere a living faith and a spectacular devotion, not completely devoided of the Hindu exhibitionism. The images in the houses of the poor and the oratories, sometimes real chapels, in the dwellings of the rich complete this Christian profile in their intimate life. The Hindu temples, on the contrary, built near the springs of water and rivers needed for the ritual ablutions, are nearly always a quiet presence, dissimulated among the sacred trees and half hidden in the fold of the ground which forms the bottom of the valley. On one hand, it is known how the coming of powerful rivals - the Dutch and the English - and on the other hand, the advent of the Mahratta Empire keeping in with the small territory of the Old Conquests, led the Viceroys to extend their dominion up to the natural border - the edge of Ghatsbuilding around it a safe area which permitted the Hindu people to continue observing their religion, habits and custom and even in most cases their feudal organization. The New Conquests, in spite of the penetration thus facilitated by the peaceful existence of two different worlds have remained in great part faith ful to the Hindu tradition. Such is the Christianized land which for more than four centuries and half has consti tuted its most original feature as far as the outline of Goa is concerned. Goa has a surface of 3500 km² and 550.000 inhabitants. At present, the Christians of the Old Conquests form 60/100 of the population and those of the New Conquests 15/100. They also made of Goa their nucleous of emigration which through almost one hundred thousand people scattered all over India, Pakistan, Persian Gulf, East Africa and the whole Portugues world would confer to this minute place an unexpected irradiation. But between the earlier conquered and more deeply assimilated patch of Portuguese land and that of the late and quiet occupation verified when the evangelical dream had gone into pieces, there are other oppositional components: 59/100 of the population over 22/100 of the land of the Old Con quests where the four towns of Goa have been built be sides the ruins of the old capital, giving an average of 441 inhabitants per km², against 79 of the New Conquests; but in the Christian land, extension of the almost barren lateritic plateaux, there are also vast plains of rice and palm trees which support the income of rich village com munities whereas in the Hindu land, the woods cover a more marked relief, and on its poor soil both the itinerant agriculture and the extensive tending of the flocks as well are practised; the plains, much smaller, are less coveted by the high castes, whom the organization of communities is due to. A feudal system of rendering of personal service to ancient knights replaces, in several cases, the previous existing one. The contrast, partly motivated by the territorial organization around a big city, is essentially formed by two more or less inhabited areas; but the enlargement of the valleys which cut the mountainous border and form along the estuaries vast alluvial plains ready to be tilled, is the natural feature which permitted to raise the littoral region to an integral organization of space as well as to a strong density of population. Both have supported in its turn the prosperity of Goa (important city under the Mohammedan rule at the date of its conquest) and this in its turn has still further increased the agricultural occupation of its periphery. When it passed to the Portuguese dominion these laads extraordinarily fertile and considered the best ones of Concao have ensured to their new owners as well as to the local converted population chained to their destiny a basis of subsistence. Among either the indifferent or hostile hinduism, the Christian places were profusely covered with symbols of the new religion. A strange belief threw into this small portion of India deep roots which at first sight may surprise the most superficial observer, i. e. how one of the components of civilization brought from so far and trans planted by force, has stuck to it in such a way that the scenery itself has adopted it as one of its characteristic signs. As to the search of any ecological correlation of the religious feelings, Goa is the denial of its legitimacy. Either the hazard or the course of History have brought into contact three of the most important religions. Christendom suppressed the advance of Islamism but each one, with its abstract monotheism has left intact the rural world stuck to the tradition of a natural belief that sees in each tree, spring or stone either the image or the conception of a powerful and protecting God.